Optical manipulation of chiral nanoparticles in vector Airy beam. (6th November 2018) - Lu, Wanli; Sun, Xu; Chen, Huajin; Liu, Shiyang; Lin, Zhifang
Abstract: The optical manipulation of chiral nanoparticles in a vector Airy beam with linear polarization is theoretically investigated, and to calculate the optical forces acting on a spherical chiral particle of an arbitrary size beyond the paraxial approximation, a rigorous numerical method based on the generalized Lorenz–Mie theory and Maxwell stress tensor method is presented. It is found that the chiral nanoparticle not only can be stably trapped within the main lobe due to the transverse optical gradient force but also can be transported faster than a conventional particle without chirality along curved trajectories because of the longitudinal scattering optical force. In addition, the particle chirality significantly enhances the longitudinal optical force while slightly affecting the transverse optical force. Our results may provide an additional handle for the optical manipulation of chiral nanoparticles.